Campus sexual assault : constitutional rights and fundamental fairness / Evan Gerstmann. - Gerstmann, Evan (Cambridge University Press, 2019)
Sexual assault on college campuses has drawn tremendous public attention and colleges are under great pressure to respond. In many cases, the result has been a system of sexual assault tribunals that violates the rights of alleged assailants and assault survivors. Gerstmann shows how colleges are often punishing students as sex offenders without a fair hearing and are defining sexual offenses in an unconstitutionally broad manner. Using unbiased and accessible language, this book avoids easy answers and asks: how are colleges failing to assess accusations in a fair manner? Why are 'affirmative consent' laws unconstitutional? How can we do a better job preventing sexual assault? The author argues that colleges are too often making poor choices in terms of how they respond to allegations of sexual assault and, in doing so, they are depriving students of due process, while failing to protect victims of assault.